Refugee health care : an essential medical guide - Annamalai, Aniyizhai (Springer New York, 2014)
Refugees arriving in the U.S. are required to undergo medical screening soon after arrival and also need ongoing health care. Medical examination of refugees differs from routine patient evaluations in significant ways: * They often come from countries with a disease epidemiology different from the U.S. * They should be screened for communicable diseases upon arrival * The prevalence of mental health disorders in refugees is high * Medical and psychiatric conditions of refugees are affected by past trauma and current acculturation difficulties * Significant cultural barriers can arise in the accurate evaluation and treatment of refugees. Physicians receive very little training in refugee health. Refugee Health Care is a practical guide providing concise information for busy practitioners. This concise textbook reviews common conditions seen in refugees and some of the recommendations in the book apply to all immigrants. It will be a valuable resource for primary care physicians, psychiatrists, pediatricians, women's health providers and any health care practitioner who treats refugees.